Performance of two new block implicit procedures for the treatment of the velocity-pressure coupling problem in incompressible fluid flow - Mazhar, Z (Wit Press, 2002)
The performance of two new non-segregated, block implicit procedures; BIP [1] and BIPEN [2] are compared with the well known SIMPLER procedure, applied to benchmark problems of various sizes. It is demonstrated that BIP provides quicker convergence than SIMPLER by a factor of two, and BIPEN is %40 faster than BIP. In addition it is shown that both methods are extremely robust, even for large-sized problems, rendering them as a basis for a new generation of hybrid computation algorithms, for the efficient treatment of the velocity-pressure coupling problem.
4th International on Advances in Fluid Mechanics -- MAY, 2002 -- GHENT, BELGIUM
Keywords: Equations